THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND THE QUALITY OF LIFE OF STROKE PATIENTS IN THE NERVOUS CLINIC AND STROKE UNIT OF THE RSUD - Khoiru Ulfah,; Nurhusna,; Andika Sulistiawan,; Yulia Indah Permata Sari,; Satria Saputra, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Stroke is a leading non-communicable disease that causes disability and death worldwide. It leads to physical impairments such as paralysis and speech difficulties, along with psychological impacts like depression, anxiety, and loss of purpose. Stroke survivors must adapt to changes in physical function and social roles, where family support plays a vital role in providing motivation, emotional stability, and assistance with daily activities. Strong family support can enhance morale, treatment adherence, and overall quality of life. To analyze the relationship between family support and quality of life among stroke patients treated at the Neurology Clinic and Stroke Unit of Raden Mattaher Regional General Hospital, Jambi. This analytical observational study used a cross-sectional design with 90 respondents selected through accidental sampling. Data were collected using two instruments: a Family Support Questionnaire based on House’s theory (1981) and the Stroke Specific Quality of Life (SS-QOL) questionnaire. The Spearman Rank correlation test was applied for data analysis. Most participants reported good family support (78.9%) and good quality of life (76.7%). Statistical analysis showed a strong and significant correlation between family support and quality of life (r = 0.799; p = 0.000). There is a strong positive relationship between family support and the quality of life of stroke patients at Raden Mattaher Regional General Hospital. Enhanced family support contributes significantly to better adaptation and improved well-being among stroke survivors